2004
DOI: 10.4081/ijas.2004.47
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of enterotoxin genes and macrorestriction analysis of Staphylococcus aureus isolated from bovine mastitis and bulk-tank milk samples in Italy. An epidemiological study

Abstract: The goal of the study was to genotypically compare S. aureus isolates from mastitis milk and raw milk to identify the
relation between strains and to assess the enterotoxigenicity of the isolates. Eighty-three Staphylococcus aureus isolates
recovered from cows and bulk tank milk of five farms in northern Italy were compared genotypically. The genes for the
enterotoxins A, D, G and I, but not for B, C, E and H and the toxic shock syndrome toxin 1 (TSST-1), were detected by
PCR amplification.…
Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…Th e most frequently observed SE was SEA, observed in 12 samples (16.7%), followed by SED (9 samples, 12.5%) and SEC (6 samples, 8.3%). Th ese fi ndings are in agreement with Normano et al (13), Morandi et al (8), and Serraino et al (14), who reported frequent fi ndings of enterotoxins A and D in many cow dairy products. However, some of our fi ndings diff ered from those reported by other researchers in other countries.…”
Section: Sample Testedsupporting
confidence: 90%
“…Th e most frequently observed SE was SEA, observed in 12 samples (16.7%), followed by SED (9 samples, 12.5%) and SEC (6 samples, 8.3%). Th ese fi ndings are in agreement with Normano et al (13), Morandi et al (8), and Serraino et al (14), who reported frequent fi ndings of enterotoxins A and D in many cow dairy products. However, some of our fi ndings diff ered from those reported by other researchers in other countries.…”
Section: Sample Testedsupporting
confidence: 90%
“…On the other hand, higher contamination rates have also been found [ 35 - 39 ]. The contamination of milk can be internally through the secretion of milk from the infected animal or externally through the infected persons (approximately, 50% of the human population carries S. aureus as commensals) or through the environment (soil, water, dust, and air) [ 40 ]. Milk and milk products are widely consumed since ancient times and its market demand is continuous worldwide [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…aureus represents one of the most famous microorganisms found in raw milk, that milk offers a suitable medium for this bacterium growth especially when decreasing of hygienic measures as well as of cooling services occurred (16). Milk contamination could be internal through infected animals' secretion, or external due to infected persons because of the commensalism the human population and S. aureus bacteria that approximately 50% of the people are S. aureus carriers, or might cause through the environment such as water, air, soil or dust (17).…”
Section: Discussionmentioning
confidence: 99%